What do adolescents think about decent work and inclusion? A qualitative study - Zammitti, Andrea; Agosta, Giuseppina; Ferlito, Carmela; Todaro, Oriana Maria; Caruso, Alfio; Taibi, Teresa; Catania, Daniela (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Recently, within the Life Design paradigm, particular attention has been given to the construction of inclusive and sustainable futures and the design of counselling interventions for the promotion of a decent life for everyone. In this perspective, decent work is conceptualized as productive, innovative, creative, safe and protected work, but also as the opportunity to build inclusive and sustainable societies. Among the challenges of the future that young people will have to face are those of inclusion and difficult access to decent work. The aim of this research was to explore the ideas of inclusion and decent work of a group of adolescents (N = 300, age between 17 to 19) from eastern Sicily in transition phase between secondary school and the world of work or university.